2013
DOI: 10.4236/jbnb.2013.41001
|View full text |Cite
|
Sign up to set email alerts
|

Sintering and Mechanical Properties of Magnesium and Fluorine Co-Substituted Hydroxyapatites

Abstract: Biological apatites contain several elements as traces. In this work, magnesium and fluorine co-substituted hydroxyapatites with the general formula Ca 9 Mg(PO 4 ) 6 (OH) 2-y F y , where y = 0, 0.5, 1, 1.5 and 2 were synthesized by the hydrothermal method. After calcination at 500˚C, the samples were pressureless sintered between 950˚C and 1250˚C. The substitution of F − for OH − had a strong influence on the densification behavior and mechanical properties of the materials. Below 1200˚C, the density steeply d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…The a variation was governed by two antagonist effects: firstly, the substitution of K + (0.138 nm) for Ca 2+ (0.100 nm) induced an increase in the a values; however, as it was reported in the literature, the substitution of a divalent cation by a monovalent one decreased the channel diameter of a parameter and in consequence, a markedly decreased [28,29,31]. Secondly, the bibliography on hydroxfluorapatites reported that a parameter increased with a decreasing degree of fluoridation [36,37]. In present work, a contraction of the lattice parameters suggested was attributed to K + substitution.…”
Section: Phase Analysismentioning
confidence: 82%
“…The a variation was governed by two antagonist effects: firstly, the substitution of K + (0.138 nm) for Ca 2+ (0.100 nm) induced an increase in the a values; however, as it was reported in the literature, the substitution of a divalent cation by a monovalent one decreased the channel diameter of a parameter and in consequence, a markedly decreased [28,29,31]. Secondly, the bibliography on hydroxfluorapatites reported that a parameter increased with a decreasing degree of fluoridation [36,37]. In present work, a contraction of the lattice parameters suggested was attributed to K + substitution.…”
Section: Phase Analysismentioning
confidence: 82%
“…[20][21][22] Sheline [23] confirmed that the molten magnesium fluoride facilitates the decomposition of magnesia by investigating the electrolytic production of Mg from MgO both experimentally and theoretically. Wang [24] provided experimental evidence that magnesium fluoride is generated during the reduction of magnesia with 3 wt pct CaF 2 .…”
Section: Role Of Fluorine and Calcium Ionsmentioning
confidence: 89%
“…On the other hand, F − was combined with Ag + , Mg 2+ and Y 3+ in order to be co‐substituted within apatite lattice. Turkoz et al synthesised silver and fluoride doped hydroxyapatites by precipitation and verified that small amount of dopings resulted in high densities and fine grain microstructures, and that Ag + and F − ions incorporation led to increased microhardness values with respect to undoped HAp.…”
Section: Bi‐substituted Hydroxyapatite Powdersmentioning
confidence: 99%
“…Turkoz et al synthesised silver and fluoride doped hydroxyapatites by precipitation and verified that small amount of dopings resulted in high densities and fine grain microstructures, and that Ag + and F − ions incorporation led to increased microhardness values with respect to undoped HAp. Nsar et al produced magnesium and fluorine co‐substituted hydroxyapatites (Ca 9 Mg(PO 4 ) 6 (OH) 2− y F y , where y = 0, 0.5, 1.0, 1.5 and 2.0) by the hydrothermal method. They highlighted that the thermal stability, microstructure, sinterability, and mechanical properties strongly depend on the temperature of the thermal treatment and on the fluorine amount.…”
Section: Bi‐substituted Hydroxyapatite Powdersmentioning
confidence: 99%